Photosynthetic activity and dynamics of dry mass of plants accumulation of winter soft wheat, depending on growing conditions - E. V. Ionova; V. L. Gaze; V. А. Likhovidova (Зерновое хозяйство России)
The current paper has considered the effect of various growing conditions (insufficient and optimal moisture) on the leaf area of winter wheat plants, photosynthetic potential, net photosynthesis productivity and dry mass of plants. The objects of the study were the winter soft wheat samples (12 genotypes) developed by the FSBSI “Agricultural Research Center “Donskoy”. The study of the samples was carried out by the V. V. Maimistov method (1988), namely a testing of varieties for drought tolerance in the conditions of model drought “zasushnik”; by the A. Nichiporovich method (1955), namely a determination of leaf area, photosynthetic potential and net productivity of photosynthesis; by the B. Yagodin method (1987), namely a determination of dry matter of plants. Mathematical data processing was carried out according to the B. A. Dospekhov method using the program Statistica 10. The purpose of the study was to establish the winter soft wheat genotypes with high resistance of the leaf system of plants to unfavorable environmental factors. According to the study results, there have been identified the winter soft wheat samples “Yubiley Dona”, “Zodiak” and “586/13” which, under conditions of insufficient moisture supply during the growing season (“head formation - waxy ripeness of kernels”), had the maximum values of the following indicators: leaf area (202.0 cm2, 193.3 cm2 and 174.5 cm2), photosynthetic potential (0.528 million m2/day, 0.559 million m2/day and 0.560 million m2/day) and dry mass of plant leaves (1315.0 g, 1329.0 g and 1280.4 g). Due to the net productivity of photosynthesis (under insufficient moisture supply), the highest values of this indicator were identified in the winter soft wheat samples “1074/11” (20.16 g/m2 per day), “Univer” (19.43 g/m2 per day) and “Ambar” (19.33 g/m2 per day).